2018
DOI: 10.5539/elt.v11n12p211
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Learning Strategies (VLSs) Preferred by Saudi EFL Students

Abstract: The aim of this study is to identify Vocabulary Learning Strategies (VLS) that seem to be used more frequently by Saudi undergraduate English as a Foreign Language (EFL) students and to discuss the sub-strategies amongst the main five strategies identified by Schmitt’s (1997) taxonomy of VLS. The population sample of 94 undergraduates was selected from Al Jouf University with the use of quantitative survey methodology. The questionnaire was designed based on Schmitt’s (1997) taxonomy, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
4
1
1
Order By: Relevance
“…Gil (2022) found that the determination strategy was the most employed strategy, and the least used strategy was the metacognitive strategy. Nevertheless, the result of this research contradicts the result obtained by (Al-Bidawi, 2018), which found that the first most used were social strategies, and the second most used category was cognitive strategies.…”
Section: Discussioncontrasting
confidence: 99%
“…Gil (2022) found that the determination strategy was the most employed strategy, and the least used strategy was the metacognitive strategy. Nevertheless, the result of this research contradicts the result obtained by (Al-Bidawi, 2018), which found that the first most used were social strategies, and the second most used category was cognitive strategies.…”
Section: Discussioncontrasting
confidence: 99%
“…Vocabulary learning is a daily activity among undergraduate learners from various Saudi universities (Alhaisoni, 2012). Similar to other universities in all places, EFL learners face a lot of challenges in gathering required knowledge and volumes of vocabulary that will enable them to adequately comprehend the second/foreign language effectively in their various fields of endeavors (Al-Bidawi, 2018). Saudi undergraduate EFL learners struggle with vocabulary learning due to a lack of breadth and depth of vocabulary awareness, which is commonly associated with the frequency of vocabulary memorization and the pattern of strategy memorization (Al-Bidawi, 2018;Alqarni, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
“…Similar to other universities in all places, EFL learners face a lot of challenges in gathering required knowledge and volumes of vocabulary that will enable them to adequately comprehend the second/foreign language effectively in their various fields of endeavors (Al-Bidawi, 2018). Saudi undergraduate EFL learners struggle with vocabulary learning due to a lack of breadth and depth of vocabulary awareness, which is commonly associated with the frequency of vocabulary memorization and the pattern of strategy memorization (Al-Bidawi, 2018;Alqarni, 2019). As a result of these issues, Saudi undergraduate learners have problem in remembering the words at point of need, particularly for writing academic documents (e.g.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Avrupa Ortak Dil Kriterlerine göre mevcut olan 6 dil düzeyi aşağıda gösterilmektedir: Yabancı dil(ler)in eğitimi sürecinde kelime öğretim alanlarıyla ilgili ulusal ve uluslararası literatür incelendiğinde daha önce yayınlanmış araştırmalar arasında ilk grupta İngilizce eğitiminde kelime bilgisinin geliştirilmesine yönelik yayınlanmış çalışmalar mevcuttur (Zengin, 2019;Akmaz;Al-Bidawi, 2018;Ketevan, 2018;Zorluel Özer & Cabaroğlu, 2018;Albar, 2017;Demir, 2017;Gök, 2017;Kansızoğlu, 2017;Maghsoudi & Golshan, 2017;Mashhadi Heidar & Sadeghzadeh Hemayati, 2017;Patahuddin, Syawal & Bin-Tahir, 2017;Patterson, 2017;Baldoumi, 2016;Işık, 2016;Işık & Semerci, 2016;Tosun, 2016;Anadol, 2015;Başören, 2015;Çelik, 2015;Ebrahimi & Azhideh, 2015;Hemmati & Asmawi, 2015;Hişmanoğlu, 2015;Şimşek, 2015;Wang, Theng & Chen, 2015;Al-Darayseh, 2014;Kocaman & Kızılkaya Cumaoğlu, 2014;Özdemir, 2014;Sarı Atilla, 2014;Aktekin & Güven, 2013;Amirian & Heshmatifar, 2013;Shintani, 2013;Tayhani Temizgöl, 2013;Akkakason, 2012;Gülten, 2012;Heidari, & Tavakoli, 2012;Ping & Siraj, 2012;…”
Section: Introductionunclassified